Contrasting properties of hydrogenated and protonated single-layer h-BN from first-principles. (12th January 2018) - Zou, Juan; Tang, Li-Ming; Chen, Keqiu; Feng, Yexin
Abstract: Hydrogenation is an efficient approach to tune the electronic, magnetic and chemical properties of single-layer hexagon boron nitride (h-BN). The relative stabilities and electronic properties of hydrogenated and protonated h-BN sheets are studied by means of density functional theory calculations. H and H + show very contrasting behaviors in chemisorption and clustering on h-BN, in which a single H atom prefers to adsorb on the top site of the boron (B) atom, and more H atoms tend to cluster on both sides of the h-BN layers in an alternating manner; while single H + prefers to stay on the nitrogen (N) atom, and protons are more likely to separate from each other on h-BN. The collective s p 3 bonding feature of H-decorated h-BN lattice plays a key role in stabilizing the H clusters on the h-BN sheet. The non-magnetic H clusters with an even number of H atoms ( N H ) are energetically favored, compared with those with odd N H . Both the binding energy and band gap width vary in an oscillatory way as a function of N H .